2012
DOI: 10.6023/a12040166
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic Tetrapeptides via Ligation of Peptide Hydrazides

Abstract: Naturally occurring or man-made cyclic tetrapeptides have unique rigid skeletons and therefore, represent an interesting class of candidate bioactive molecules in drug discovery. However, efficient chemical synthesis of cyclic tetrapeptides often presents a difficult problem due to the large strain involved in this category of target compounds. To overcome this problem we describe in the present study the use of peptide hydrazides for the preparation of highly strained 12-membered all-L cyclic tetrapeptides. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…Zhang and Tam proposed that the absence of oligomerization at higher concentrations resulted from the ring-chain tautomeric equilibrium of the transthioesterification step between the thioester and the thiol on N-terminal Cys. This observation was consistent with a recent study by Liu and co-workers on the synthesis of highly strained cyclic tetrapeptides by NCL . In Liu’s work, they found that cyclic monomers were formed exclusively at a concentration up to 1 mM and that significant cyclic dimer formation occurred at a concentration of 3 mM.…”
Section: Chemoselective Ligation-mediated Peptide Cyclization Creatin...mentioning
confidence: 99%
“…Zhang and Tam proposed that the absence of oligomerization at higher concentrations resulted from the ring-chain tautomeric equilibrium of the transthioesterification step between the thioester and the thiol on N-terminal Cys. This observation was consistent with a recent study by Liu and co-workers on the synthesis of highly strained cyclic tetrapeptides by NCL . In Liu’s work, they found that cyclic monomers were formed exclusively at a concentration up to 1 mM and that significant cyclic dimer formation occurred at a concentration of 3 mM.…”
Section: Chemoselective Ligation-mediated Peptide Cyclization Creatin...mentioning
confidence: 99%
“…Natural charge: The atom natural charge of compounds are given in Table-3. These data show that, the negative charge is mainly concentrated in the C(1) of pyrimidine ring, N(2), N (5) and N(6) of triazine ring, and C(7), C(8), C (11) and C(12) of benzene ring. These atoms make the electronegative area, they could combine with positive area of receptor.…”
Section: Quantitative Structure-activity Relationships Of the Trisubsmentioning
confidence: 82%
“…For pesticide molecules, too low-E LUMO or too high-E HOMO means that the molecule itself activity is too strong, it is easy to be metabolized in organism. The effect of pesticide is difficult to control, so the E LUMO or E HOMO of the pesticide molecule should be suitable to estimate expected value [10][11][12] .…”
Section: Quantitative Structure-activity Relationships Of the Trisubsmentioning
confidence: 99%
“…Thus, four cyclic tetrapeptides containing all L-amino acids cyclo(L-Cys-L-Leu-L-Ala-L-Leu), cyclo(L-Cys-L-His-L-Gly-L-Trp), cyclo(L-Cys-L-Val-L-Gly-L-Ile) and cyclo(L-Cys-L-His-L-Trp-L-Gly) have been successfully prepared in moderate yields (∼40%) through intramolecular native chemical ligation (NCL) (Scheme 6). 56,57 Fmoc-SPPS on a hydrazine 2-chlorotrityl resin (26) was used to prepare the peptide hydrazide (27) and its conversion to acyl azide (28) in solution followed. The peptide hydrazide was used as a precursor to the corresponding peptide thioester (29), which undergo NCL (30) to afford the corresponding cyclotetrapeptide (31).…”
Section: Ring Contraction Strategiesmentioning
confidence: 99%